2014
DOI: 10.1073/pnas.1400178111
|View full text |Cite
|
Sign up to set email alerts
|

Impact of puberty on the evolution of cerebral perfusion during adolescence

Abstract: Puberty is the defining biological process of adolescent development, yet its effects on fundamental properties of brain physiology such as cerebral blood flow (CBF) have never been investigated. Capitalizing on a sample of 922 youths ages 8-22 y imaged using arterial spin labeled MRI as part of the Philadelphia Neurodevelopmental Cohort, we studied normative developmental differences in cerebral perfusion in males and females, as well as specific associations between puberty and CBF. Males and females had con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
185
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 188 publications
(223 citation statements)
references
References 76 publications
(97 reference statements)
20
185
4
Order By: Relevance
“…To date, however, only a handful of nuclear medicine studies (Chiron et al, 1992;Chugani, 1998;Takahashi et al, 1999;Wintermark et al, 2004) reported developmental changes in CBF, CMRglu and CMRO 2 , suggesting a general peak around 5-8 years followed by tapering to adult levels throughout adolescence. Similar developmental trajectories of resting CBF have recently been shown by ASL perfusion MRI studies (Avants et al, 2015;Biagi et al, 2007;Satterthwaite et al, 2014;Taki et al, 2011aTaki et al, , 2011bWang and Licht, 2006;Wang et al, 2003). Detailed region and sex specific developmental trajectories of CBF have been revealed after the effect of age-related variations in cortical structure was adjusted (Satterthwaite et al, 2014;Taki et al, 2011aTaki et al, , 2011b.…”
Section: Developmental Trajectories Of Cbf and Cmro 2 At Baselinesupporting
confidence: 75%
See 2 more Smart Citations
“…To date, however, only a handful of nuclear medicine studies (Chiron et al, 1992;Chugani, 1998;Takahashi et al, 1999;Wintermark et al, 2004) reported developmental changes in CBF, CMRglu and CMRO 2 , suggesting a general peak around 5-8 years followed by tapering to adult levels throughout adolescence. Similar developmental trajectories of resting CBF have recently been shown by ASL perfusion MRI studies (Avants et al, 2015;Biagi et al, 2007;Satterthwaite et al, 2014;Taki et al, 2011aTaki et al, , 2011bWang and Licht, 2006;Wang et al, 2003). Detailed region and sex specific developmental trajectories of CBF have been revealed after the effect of age-related variations in cortical structure was adjusted (Satterthwaite et al, 2014;Taki et al, 2011aTaki et al, , 2011b.…”
Section: Developmental Trajectories Of Cbf and Cmro 2 At Baselinesupporting
confidence: 75%
“…Similar developmental trajectories of resting CBF have recently been shown by ASL perfusion MRI studies (Avants et al, 2015;Biagi et al, 2007;Satterthwaite et al, 2014;Taki et al, 2011aTaki et al, , 2011bWang and Licht, 2006;Wang et al, 2003). Detailed region and sex specific developmental trajectories of CBF have been revealed after the effect of age-related variations in cortical structure was adjusted (Satterthwaite et al, 2014;Taki et al, 2011aTaki et al, , 2011b. These studies suggest that ASL CBF may provide a valuable imaging marker of both typical and atypical development of brain function (Wang et al, 2009).…”
Section: Developmental Trajectories Of Cbf and Cmro 2 At Baselinesupporting
confidence: 72%
See 1 more Smart Citation
“…Consistent with these findings, we have performed a comprehensive analysis on the structural connectome to elucidate sex differences in terms of individual connections [17], revealing stronger intrahemispheric connectivity (within both hemispheres) in males and stronger inter-hemispheric connectivity in females. The developmental course of sex differences is a less explored domain [11], mostly due to lack of large datasets spanning age ranges that include the developmental period, with a few exceptions in the case of structural, functional and behavioural modalities [11,16,17,21,32].…”
Section: Introductionmentioning
confidence: 99%
“…In support of this concept, there is growing evidence that in humans and experimental animals, the origins of pathologies associated with structural weakening of the vascular wall (e.g., intracerebral hemorrhages) occur during puberty, a time of rapid changes in the cerebral circulation and structural brain development (Blakemore et al 2010;Blanton et al 2012;Giedd et al 2006;Goddings et al 2014;Manz et al 1979;Peper et al 2011;Satterthwaite et al 2014). …”
Section: Discussionmentioning
confidence: 99%